Convict Criminology at the Crossroads: Research Note. (March 2013) - Newbold, Greg; Ross, Jeffrey Ian
This research note critiques both the past and current status of Convict Criminology. It notes the subtle changes that have occurred within this approach to the study of corrections and the criminal justice system and some of the controversies that have emerged. It discusses these issues and makes recommendations about Convict Criminology's future direction.